Ett ”väl utsmyckat skrin” för Katarina av Vadstena? En omtolkning av det broderade relikvariet i Linköpings domkyrkomuseum - Eva Lindqvist Sandgren (ICO Iconographisk Post, 2019)
Title in English: A “well adorned shrine” for St Katarina of Vadstena? A reinterpretation of the embroided reliquary in Linköping Diocesan Museum